2021
DOI: 10.1016/j.jare.2021.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and immunological characterization of bluetongue virus serotype 1 infection in type I interferons blocked immunocompetent adult mice

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…29 The histopathological lesions were marked necrosis in tunica media of pulmonary artery and aorta, congestion, mononuclear cells infiltration, capillary damage with haemorrhages and oedema, and perivascular cuffing seen in this study, which can be correlated to the earlier studies. 28 Further, in this study on 7 dpi, endothelial cells of the major vessels were found swollen, which may be due to hypertrophy leading to sloughing of these cells into the lumen of arteries, which can be related to the study done by Saminathan et al 30 Presence of BTV antigen in the arteries was confirmed by immunohistochemistry and RT-PCR. As per the previous studies for locating the BTV antigen in blood vessels, it was seen that endothelial cells of capillaries and arterioles were mostly associated with the antigen.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…29 The histopathological lesions were marked necrosis in tunica media of pulmonary artery and aorta, congestion, mononuclear cells infiltration, capillary damage with haemorrhages and oedema, and perivascular cuffing seen in this study, which can be correlated to the earlier studies. 28 Further, in this study on 7 dpi, endothelial cells of the major vessels were found swollen, which may be due to hypertrophy leading to sloughing of these cells into the lumen of arteries, which can be related to the study done by Saminathan et al 30 Presence of BTV antigen in the arteries was confirmed by immunohistochemistry and RT-PCR. As per the previous studies for locating the BTV antigen in blood vessels, it was seen that endothelial cells of capillaries and arterioles were mostly associated with the antigen.…”
Section: Discussionsupporting
confidence: 74%
“…As per the previous studies for locating the BTV antigen in blood vessels, it was seen that endothelial cells of capillaries and arterioles were mostly associated with the antigen. 30 In the present study, larger arteries like aorta and pulmonary artery were found positive for BTV antigen by immunohistochemistry.…”
Section: Discussionsupporting
confidence: 61%
“…Notwithstanding other virulence factors, the differential virulence observed in cattle between the viral isolates used in this work could be partly explained by a differential immunomodulation of the host IFN response, which eventually might or not restrict host range. Although it can help explain the inability of EHDV-8 to infect A129 mice, the differential immunomodulation of the host IFN response cannot explain our results in IFNAR(-/-) mice, whose susceptibility to other orbiviruses such as BTV depends on an impaired IFN-I response 50 , 52 . Therefore, other virulence determinants must be involved in the differential virulence between these viruses.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, BTV-related leukopenia has also been reported in interferon deficient mouse models of infection ( Saminathan et al. 2020 b; Saminathan et al., 2021 ). This immune suppression is thought to be driven by follicular dendritic cells as was observed in a sheep model of BTV-8 infection ( Melzi et al., 2016 ).…”
Section: Discussionmentioning
confidence: 95%